NAVIGATING THE COMPLEX LANDSCAPE OF HUMAN RESOURCES MANAGEMENT IN INDONESIA: LITERATURE REVIEW STUDY - Wahyudin, Ferdic Sukma (JURNAL ILMIAH EDUNOMIKA, 2023)
This literature review navigates the intricate landscape of Human Resources Management (HRM) in Indonesia, comprehensively analyzing the existing body of knowledge. The study explores various facets of HRM, including recruitment, training, performance appraisal, and employee relations, within Indonesia's unique cultural and socio-economic context. By synthesizing insights from scholarly articles, books, and relevant sources, the review provides a nuanced understanding of the challenges, best practices, and emerging trends in HRM specific to Indonesia. Additionally, it critically examines the cultural influences on HRM practices, acknowledging the dynamic interplay between traditional values and the demands of a globalized workforce. The literature synthesis aims to offer valuable insights for practitioners, policymakers, and researchers engaged in the field of HRM in Indonesia, contributing to the ongoing discourse on effective human resource strategies in diverse organizational settings. Keywords: Human Resources Management, Indonesia, HRM practices, Cultural influences, Workforce diversity, Organizational strategies.